2020
DOI: 10.31941/pj.v19i2.1180
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of the Supervision of the Prosecutor's Commission in Indonesia

Abstract: <table width="593" border="0" cellspacing="0" cellpadding="0"><tbody><tr><td valign="top" width="366"><p><em>This study aims to analyze the causes of the ineffective supervision carried out by the Prosecutor's Commission in an effort to improve the performance of the Public Prosecutors Office of the Republic of Indonesia. The facts show that there are many negative public reports and complaints regarding the performance of the AGO. These reports are examined first, before be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Second, joint ownership without legal bonds among the owners. (Iswantoro, Saputra, Doyoharjo, & Luthviati, 2020) Based on the description above, the implementation of horizontal separation can be applied in Apartment Law because it is in line with the principle the BAL adheres to, however, in practice, the joint land ownership in Apartment Law is different from that in BAL. Article 1 number 4 of Apartment Law asserts that Joint land is a land parcel for a building used based on the joint right that is not separated from the building of the apartment in which the boundaries have been determined in the building permit.…”
Section: Horizontal Separation Principle In Regulation Concerning Apartmentmentioning
confidence: 99%
“…Second, joint ownership without legal bonds among the owners. (Iswantoro, Saputra, Doyoharjo, & Luthviati, 2020) Based on the description above, the implementation of horizontal separation can be applied in Apartment Law because it is in line with the principle the BAL adheres to, however, in practice, the joint land ownership in Apartment Law is different from that in BAL. Article 1 number 4 of Apartment Law asserts that Joint land is a land parcel for a building used based on the joint right that is not separated from the building of the apartment in which the boundaries have been determined in the building permit.…”
Section: Horizontal Separation Principle In Regulation Concerning Apartmentmentioning
confidence: 99%
“…In general, the basis used by the judge to impose the death penalty as a recycled ratio, such as the perpetrator's actions are classified as serious crimes, planned, carried out sadistically, preceded and followed by violence until the loss of the victim's life, these things are based on legal logic and facts. (Iswantoro, Saputra, et al, 2020) Legal facts revealed in the evidence before the court session, including anything that mitigating and incriminating for the defendant, but not detailed. These matters missed the judge's judgment.…”
Section: 2legal Reconstruction Requirements/criteria For Criminal Offenders Sentenced To the Death Penalty In The Futurementioning
confidence: 99%
“…Meanwhile, the anti-death penalty group (abolitionist group) based on philosophical-theological humanitarian reasons by taking refuge behind the justification of human rights. (Iswantoro, Saputra, Doyoharjo, & Luthviati, 2020) The most common criminal offenses in Indonesia for which the defendants still charged with the death penalty are cases of premeditated murder as regulates in Article 340 of KUHP where the act preceded, followed and accompanied by violence following the fulfillment of elements of Article 89 of KUHP, or accompany criminal acts such as robbery, severe abuse, mutilation, rape, and others. (Triwanto & Aryani, 2020) Meanwhile, the development of crimes committed by combining science and technology in the flow of globalization, such as the flow of advances in information and technology, with a correlated mode as a means of supporting unconventional crimes, appears fertile and is used by criminals with qualifications for new types of special-crimes.…”
Section: Introductionmentioning
confidence: 99%
“…Those who violate the law will be imposed to penalty. (Iswantoro, Saputra, Doyoharjo, & Luthviati, 2020) However, a person indicated to have committed a criminal act, either committing a prohibited act or not carrying out an obligation according to the criminal law, is not absolutely subject to criminal penalties. For that reason, the law enforcement is essential to ensure whether the person has committed a criminal act or not.…”
Section: Introductionmentioning
confidence: 99%